Analytical estimation on damping behaviors of the Self-Damping fiber reinforced polymer (FRP) cable. (June 2020) - Yang, Yaqiang; Fahmy, Mohamed F.M.; Pan, Zhihong; Guan, Sujun; Zhan, Yang
Abstract: This paper analytically estimates the damping behaviors of a new type of self-damping fiber reinforce polymer (FRP) cables. Based on the vibration results of scale-model dynamic tests, the modal damping ratios of non-self-damping FRP cable were firstly analyzed using the modified formula of the self-damping FRP cables and the combined Rayleigh and frequency independent damping (CRFID) model. According to the energy dissipation mechanism and structural characteristics of the self-damping FRP cable, analysis modal damping models are proposed. Compared with the test results, the availability of the analysis models is verified. The results indicated that: the damping coefficient of the dynamic strain of a non-self-damping FRP cable is larger than that of a steel cable and a basalt FRP (BFRP) cable, and smaller than that of the carbon FRP (CFRP) cable; the proposed model can effectively evaluate the damping ratios of the in-plane vibration of a self-damping FRP cable under different amplitudes; and the damping ratios of the out-of-plane vibration of self-damping and non-self-damping FRP cables can be well predicted using the CRFID model.